2015
DOI: 10.1103/physrevb.91.035413
|View full text |Cite
|
Sign up to set email alerts
|

Generation of subsurface voids and a nanocrystalline surface layer in femtosecond laser irradiation of a single-crystal Ag target

Abstract: Structural transformations in a shallow surface region of a bulk Ag (001) target irradiated by a femtosecond laser pulse are investigated in large-scale atomistic simulations and experiments.The simulations reveal a complex interplay of fast laser melting, rapid resolidification, and the dynamic relaxation of laser-induced stresses that leads to the formation of a sub-surface porous region covered by a nanocrystalline surface layer. The generation of the porous region is consistent with the experimental observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 100 publications
11
119
1
Order By: Relevance
“…These calculations do assume that the temperature of material where dislocation is gliding remains within 300-900 K. Temperature profile estimates from molecular dynamics simulations in metallic systems, 15 which have much higher thermal conductivities than dielectrics, provide an upper bound on heating due to femtosecond laser ablation. At depths greater than 100 nm below the ablated surface for gold targets, the temperature profile remains below 1000 K. Therefore, the high temperatures experienced during femtosecond laser irradiation are confined to the ejected liquid-like layer in the ablating material and the very near subsurface in metals and dielectric materials, particularly at ablation threshold.…”
Section: B Dislocation Penetration Depthsmentioning
confidence: 99%
See 2 more Smart Citations
“…These calculations do assume that the temperature of material where dislocation is gliding remains within 300-900 K. Temperature profile estimates from molecular dynamics simulations in metallic systems, 15 which have much higher thermal conductivities than dielectrics, provide an upper bound on heating due to femtosecond laser ablation. At depths greater than 100 nm below the ablated surface for gold targets, the temperature profile remains below 1000 K. Therefore, the high temperatures experienced during femtosecond laser irradiation are confined to the ejected liquid-like layer in the ablating material and the very near subsurface in metals and dielectric materials, particularly at ablation threshold.…”
Section: B Dislocation Penetration Depthsmentioning
confidence: 99%
“…Femtosecond laser ablation experiments on dielectric materials have shown that material is ejected via a wide range of mechanisms, 11 which can be summarized as thermal and electrostatic in nature. 12 In the process of ejecting material from the surface, compressive and reflected tensile shockwaves are generated that propagate into the material below the ablated surface, as measured and simulated in semiconductors, 13 metals, 14,15 and dielectrics. [16][17][18] In the near-threshold ablation regime, which for STO (Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the solid-to-solid transformation origin is not involved, we also note the theoretical work of Wu et al 21 pointing out the formation of significant HCP domains in a normally FCC structure in Ag after a femtosecond laser irradiation, indicating noble metals can also remains in metastable thermodynamic states after laser exposure. The question of potential ultrafast electronic and structural transformations modifying optical, thermal and mechanical properties is a key issue in a range of observations concerning optical coupling.…”
Section: Introductionmentioning
confidence: 57%
“…2. The curves 0.5, 2 have been obtained from the estimates ( 8) and ( 11). In experiments, the bumps appear …”
Section: Solidification Of Bump Jet Formation Separation Of Dropletmentioning
confidence: 99%